2002
DOI: 10.1074/jbc.m200853200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tetrahydrobiopterin in the Regulation of Neuronal Nitric-oxide Synthase-generated Superoxide

Abstract: Tetrahydrobiopterin (H 4 B) is a critical element in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 50 publications
4
82
0
1
Order By: Relevance
“…Under these conditions, the enzyme iNOS may play a potential role in accelerating adhesion development by serving as an O 2 À -generating system instead of producing NO, by causing steady state catalysis of NADPH oxidation. 74,75 Increase in O 2 À production as a result of hypoxia may also significantly accelerate adhesion development through its rapid reaction with NO yielding ONOO - (Figure 1). 43,84 Peroxynitrite is a much more toxic reagent and attacks many cellular components, reacting with thiols and iron-sulfur centers, initiating lipid peroxidation, and promoting protein nitration via reactions with peroxidases 85,86 ( Figure 1).…”
Section: Tissue Injury Hypoxia Oxidative Stress and Transcription mentioning
confidence: 99%
“…Under these conditions, the enzyme iNOS may play a potential role in accelerating adhesion development by serving as an O 2 À -generating system instead of producing NO, by causing steady state catalysis of NADPH oxidation. 74,75 Increase in O 2 À production as a result of hypoxia may also significantly accelerate adhesion development through its rapid reaction with NO yielding ONOO - (Figure 1). 43,84 Peroxynitrite is a much more toxic reagent and attacks many cellular components, reacting with thiols and iron-sulfur centers, initiating lipid peroxidation, and promoting protein nitration via reactions with peroxidases 85,86 ( Figure 1).…”
Section: Tissue Injury Hypoxia Oxidative Stress and Transcription mentioning
confidence: 99%
“…Rosen and colleagues [42][43][44] 45 have reported that extracellular SOD is a principal regulator of the endothelium-derived NO bioavailability in conduit arteries, and extracellular SOD has been reported to be upregulated in ANG. 46 However, future studies are necessary to determine the source(s) of H 2 O 2 in these arteries.…”
Section: Nos-dependent No and H 2 O 2 Maintain Vasorelaxation In Smalmentioning
confidence: 99%
“…Active NOS3 is a homodimer that generates NO and L-citrulline from L-arginine. When exposed to oxidant stress, including peroxynitrite (ONOO -), or deprived of its reducing cofactor tetrahydrobiopterin (BH4) or substrate L-arginine, NOS3 uncouples to the monomeric form that generates O 2 -rather than NO (25,28,29). Uncoupled NOS3 is thought to be a prominent source of endothelial ROS in hypertension (19), neurohormonal stimulation, and hyperglycemia (8), and upon exposure to ONOO - (20).…”
Section: Introductionmentioning
confidence: 99%